Beyond enrolment: academic incentives, outcomes and performance in higher education - Neethling, Leigh (School of Economics, 2023)
This study examined incentives, academic outcomes, and student performance in the South African higher education (HE) sector using the University of Cape Town as a case study. The analysis was conducted using a dataset that stacked three cross-sections of first year entering students and tracked these students over time. The thesis comprises six chapters. The introductory chapter provides background content on the research. Chapter 2 presents an exploratory and descriptive analysis of the South African HE sectors over the period 2004–2015. It focuses on a descriptive analysis of key South African HE indicators and outcomes. The first objective was to evaluate access to HE by identifying the pool of potential entrants through an examination of the school-leaving cohort of each year. The second objective was to identify racial enrolment, progression, and completion patterns to observe whether significant changes occurred over the period. The author finds that the differentials in performance between racial subgroups have narrowed over time. White students are shown to have the highest student success rates at above 80%, and although other subgroups show some improvement, they do not catch up to these rates. A trend analysis of the data, however, provided support for a fall in the dropout rate for all students. This chapter also provides evidence for persistence in but slower progression through HE. Chapter 3 presents a way to consider and evaluate the Dean's Merit List (DML) incentive system in the context of an African economy. The author evaluated the impact of academic recognition policies, specifically the DML, on student outcomes. Using a regression discontinuity approach, the chapter shows that the DML as an academic incentive policy, has largely negative rather than the intended positive effects over the short- and long-term on academic performance in the South African context. The results indicate that the DML has an unfavourable impact on subsequent academic performance. Students who received the award tended to earn lower grade point averages in subsequent years than expected. The findings suggest that the DML does not reinforce academic achievement. These results appear to be counterintuitive but support Bénabou and Tirole's theoretical expectations regarding extrinsic motivation in a situation of asymmetric information between an agent and principal. Chapter 4 investigates student performance over time by introducing a ranking variable of student achievement. The main finding is that race, gender, and performance on final school leaving examinations are important determinants of academic achievement. Female students outperform male students across the distribution of grade point average, and this finding is consistent with the growing international literature. Chapter 5 presents detailed evidence on the determinants of academic outcomes using discrete-time methods for competing risks survival analysis. An important contribution of this chapter is studying the determinants of dropout and graduation in HE in the context of an African country. While graduation is the preferred route of exit, voluntary and involuntary exit before completion remain prominent for a significant number of students. Interestingly, and contrary to other international studies, the author did not find support for financial aid status contributing to either voluntary dropout or graduation, even after controlling for academic and socio-economic background factors. Students on academic programmes are shown to be more likely to be involuntarily excluded and less likely to graduate or voluntarily exit HE then mainstream students. This is a cause for concern as these programmes are an initiative intended to address transformation and equity in, HE, attracting significant resources from within and outside universities. Chapter 6 summarises and presents policy discussions. Overall, the study shows that one-size-fits-all policies within the same institution applied across heterogenous faculties do not achieve their desired outcomes in the South African HE is setting. Considerable thought should be given to the nature of recognition policies as other basic requirements, such as course progression criteria, tend to crowd out the desired incentive effects of recognition policies. In addition, academic administrators should consider programmes that promote a decrease in outcome disparities in HE, including establishing more and expanding academic development programmes.